The Influence of Intelligence Quotient and Study Habits on the Academic Achievement of Elementary School Students - Muhamad Ali Nurdin; Dimas Yanuar; Rio Andriana; Betari Indira Maharani (CV. Akademi Merdeka, 2026)
Elementary school students’ academic achievement remains a significant concern in Indonesia. The 2022 Computer-Based National Assessment indicated that many elementary school students in West Java had not yet achieved minimum competency standards in literacy and numeracy. Academic achievement is influenced by various internal factors, including cognitive ability, represented by Intelligence Quotient (IQ), and non-cognitive factors such as study habits. Although both variables have been widely examined in Western and East Asian contexts, studies investigating their simultaneous influence among Indonesian elementary school students, particularly in Cirebon City, remain limited. This study aimed to analyze the simultaneous effects of IQ and study habits on the academic achievement of students in Grades IV–VI in Cirebon City. A quantitative approach with an explanatory survey design was employed. The participants were 240 students aged 9–13 years, selected through proportionate stratified random sampling. IQ was measured using the Culture Fair Intelligence Test, while study habits were assessed using a validated questionnaire. The data were analyzed using multiple regression. The results showed that IQ (β = 0.485, p < 0.001) and study habits (β = 0.151, p = 0.008) had significant partial effects on academic achievement. Simultaneously, both variables explained 24.7% of the variance in academic achievement (R² = 0.247, F = 38.901, p < 0.001). IQ was the stronger predictor. These findings highlight the importance of strengthening both students’ cognitive abilities and study habits to improve academic achievement in elementary education.